Safety-in-numbers: An updated meta-analysis of estimates. (August 2019) - Elvik, Rune; Goel, Rahul
Highlights: Studies of safety-in-numbers are reviewed. Results are summarised by means of meta-analysis. Summary coefficients are close to 0.40 for all groups of road users. Results of primary studies are very heterogeneous. Abstract: Safety-in-numbers denotes the tendency for the number of accidents to increase less than in proportion to traffic volume. This paper updates a meta-analysis of estimates of safety-in-numbers published in 2017 (Elvik and Bjørnskau, Safety Science, 92, 274–282). Nearly all studies find safety-in-numbers, but the numerical estimates vary considerably. As virtually all studies are cross-sectional, it is not possible to determine if safety-in-numbers represents a causal relationship. Meta-regression analysis was performed to identify factors which may explain the large heterogeneity of estimates of safety-in-numbers. It was found that safety-in-numbers tends to be stronger for pedestrians than for cyclists, and stronger at the macro-level (e.g. citywide) than at the micro-level (e.g. in junctions). Recent studies find a stronger tendency towards safety-in-numbers than older studies.